Interview with Nigel Milsom, artist, Newcastle, Australia, 9 September 2017 - Messham-Muir, Kit (StudioCrasher, 2017)
Nigel Milsom is one of Australia's most extraordinary artists. He was won both of Australia's high-profile portraiture prizes, the Doug Moran (2014) and the Archibald Prize (2015). His Archibald-winning painting, titled 'Judo House Pt. 6 (The White Bird)', was a portrait of barrister Charles Waterstreet, a family friend and, for Milsom, something of a saviour. In this four-part interview, Milsom takes us from his beginnings in Sydney and Newcastle, through the highlights and ruptures in his career, to where he is today, a successful and nationally-recognised practicing artist based now in Newcastle, Australia.